The role of an aromatic group in remote chiral induction during conjugate addition of α-sulfonylallylic carbanions to ethyl crotonate - Levinger, Shlomo; Nair, Ranjeet; Hassner, Alfred (Beilstein Journal of Organic Chemistry, 2008)
The impact of a remote aromatic nucleus on the stereochemical outcome of the conjugate addition of α-sulfonylallylic carbanions to an α,β-unsaturated ester was investigated. α-Regioselectivity coupled with anti-diastereoselectivity is accompanied by a prominent preference for relative configuration 3 over 4. The 9-anthryl moiety has shown itself greatly superior over all other groups in this bias. A lithium ion–aromatic π interaction has been postulated as decisive for the remote transmission of chirality.
Keywords: cation–π interaction; conjugate addition; diastereoselectivity; regioselectivity; remote chiral induction